1992
DOI: 10.1002/pssa.2211330234
|View full text |Cite
|
Sign up to set email alerts
|

Determination of the Refractive Index and Optical Absorption Coefficient of Vapor-Deposited Amorphous AsS Films from Transmittance Measurements

Abstract: The optical transmission spectra of amorphous AsS films of composition As32S68 prepared by thermal evaporation are measured over the 0.3 to 2.0 μm spectral region. A simple straightforward procedure suggested by Swanepoel is applied for determining the index of refraction and layer thickness; the absorption coefficient is derived using the Connell and Lewis formulae based on the interference‐free transmittance. Furthermore, thickness measurements made by a surface profiling stylus are also carried out to cros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
11
1

Year Published

1995
1995
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 42 publications
(13 citation statements)
references
References 14 publications
1
11
1
Order By: Relevance
“…Therefore, one could infer that the increase in E d with increasing arsenic is due to an increase in coordination number (N c ) in the first coordination shell. It has been previously observed in As-S films that E 0 decreases and E d decreases with increasing arsenic content up to 40 at.% arsenic [28]. In this study, this trend was observed in E d but not in E 0 .…”
Section: Discussioncontrasting
confidence: 73%
“…Therefore, one could infer that the increase in E d with increasing arsenic is due to an increase in coordination number (N c ) in the first coordination shell. It has been previously observed in As-S films that E 0 decreases and E d decreases with increasing arsenic content up to 40 at.% arsenic [28]. In this study, this trend was observed in E d but not in E 0 .…”
Section: Discussioncontrasting
confidence: 73%
“…Therefore by adding S to As 2 S 3 the average bond strength of the compound increases, which causes E opt g to increase. The values of E opt g gradually decrease towards the stoichometric composition As 40 S 60 , Ramirez-Mato et al [15] have observed similar compositional dependence in the As-S cholegoenide glass system.…”
Section: Determination Of the Extinction Coefficient And Optical Bandmentioning
confidence: 59%
“…This figure can be seen that the values of refractive index gradually increase towards the stoichometric composition As 40 S 60 . Ramirez-Mato et al [15] have observed similar compositional dependence in the As-S cholegoenide glass system. Now, the values of n 2 can be fitted to a reasonable function such as the two-term Cauchy dispersion relationship, nðlÞ ¼ a þ b=l 2 , which can be used for extrapolation the whole wavelengths [16] (see Fig.…”
Section: Calculation Of the Refractive Index And Film Thicknessmentioning
confidence: 60%
See 1 more Smart Citation
“…Studies of the dependence of the optical properties of spin-coated As 2 S 3 films on illumination soon followed [9,10]. Particularly interesting is that that the index of refraction was found to depend strongly on wavelength [11] and to permanently increase by several percent after illumination [12,13].…”
Section: Introductionmentioning
confidence: 98%